Pengaruh Revitalisasi Perpustakaan Terhadap Tingkat Literasi Politik Mahasiswa - Viona, Viona Febiyola Bakkara; Darmawan Putra, Awang; Safri, Mulkan (Journal of Management and Leadership, 2025)
Library revitalization as an effort to transform physical and functional has been proven to increase reading interest and information accessibility, including in the context of political literacy. The purpose of this study is to determine the influence of library revitalization on the level of political literacy of library science students of UIN Ar-Raniry Banda Aceh. The research method uses a quantitative method with a simple linear regression approach. The population in this study is all active students of Library Science UIN Ar-Raniry Banda Aceh which totals 517 students. The sample of this study amounted to 84 active library students of UIN Ar-Raniry Banda Aceh. The use of samples uses the slovin formula taken using the purposive sampling technique. The data collection technique used in this study is using questionnaires with techniques in collecting instructions using google forms sent via direct massage and whatsaApp. The research data management technique uses a simple linear regression formula with the SPSS Version.25 program. The results of the study showed that there was a significant influence on the level of political literacy of library science students of UIN Ar-Raniry Banda Aceh by 38%. Based on the results of the research, students' understanding of politics related to politics in the era of the General Election year became effective with the influence of library revitalization. The library can be a reference for information on students' understanding of politics in the era of the General Election. Challenges ahead for libraries include ensuring the sustainability of programs and addressing digital distractions.